2010
DOI: 10.1088/0967-3334/31/9/004
|View full text |Cite
|
Sign up to set email alerts
|

Wall motion estimation in intracranial aneurysms

Abstract: Abstract. The quantification of wall motion in cerebral aneurysms is becoming important owing to its potential connection to rupture, and as a way to incorporate the effects of vascular compliance in computational fluid dynamics (CFD) simulations. Most of papers report values obtained with experimental phantoms, simulated images, or animal models, but the information for real patients is limited. In this paper, we have combined non-rigid registration (IR) with signal processing techniques to measure pulsation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…On the other hand, Oubel et al reported that the extent of wall motion of ruptured aneurysms has a higher value than that of unruptured aneu- rysms, an estimation made using digital subtraction angiography. 22 However, the values used for comparison in their report did not take into consideration the volume of the aneurysm itself. As can be seen in Figure 4A, the volume of both the aneurysm and normal arterial vessel strictly governs the amount of cardiac cycle-related volume change.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Oubel et al reported that the extent of wall motion of ruptured aneurysms has a higher value than that of unruptured aneu- rysms, an estimation made using digital subtraction angiography. 22 However, the values used for comparison in their report did not take into consideration the volume of the aneurysm itself. As can be seen in Figure 4A, the volume of both the aneurysm and normal arterial vessel strictly governs the amount of cardiac cycle-related volume change.…”
Section: Discussionmentioning
confidence: 99%
“…Even modest movement can affect the vessel walls, which might play a role in possible aneurysm rupture as was hypothesized in [35]. For realistic pulsatile flows some movement of the aneurysm walls was observed during a cardiac cycle [36]. In this chapter we take a first step and restrict to developing the IB approach for rigid geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry is defined via the masking function before starting the simulations. Experimental studies, e.g., based on measurements in medical images taken at different stages during the pulsatile cycle by [69] showed that in the human brain the movements of the arteries are rather small compared to the diameter of the cerebral vessels. However, for realistic modeling movable walls should be considered, which will in practice mean that the masking function becomes solution dependent and dynamic as well.…”
Section: Discussionmentioning
confidence: 99%
“…where u is the velocity of the fluid in the domain Ω f and it is understood that u = 0 on the vessel walls at ∂ Ω f which are taken as rigid in this study (extensions to slightly moving vessel walls were investigated in [69]). In addition, P is the pressure and Re = U r L r /ν r is the Reynolds number, in terms of a reference velocity U r , a reference length scale L r and the kinematic viscosity ν r .…”
Section: Navier-stokes Equations and Immersed Boundary Methodsmentioning
confidence: 99%
See 1 more Smart Citation